Steady and unsteady thermal analysis of a triple stack cold plate with heat losses - Beh, Shiao Lin; Ooi, C.K.; Quadir, G.A.; Seetharamu, K.N. (2005)
Purpose - To provide some new and additional data for the design of a triple stack cold plate.